What can science say about (good) dying? A defense of spiritual counselling at the end of life through the thought of Habermas and Holy Scripture - Fernández Valls, Carlos; Álvarez Moreno, Bárbara; Valls Sancho, Carmen (Razón y fe, 2023)
Science is blind to some aspects of human life, such as death as a personal and communal experience, since it cannot see beyond the end of vital functions. For this reason, the different philosophical, humanistic, and spiritual perspectives must join forces with the health sciences to be able to turn the transition into an accompaniment of the person in their last days and their families. A privileged tool for this is spiritual counselling at the end of life. In order to defend its necessity and multidisciplinarity, we will draw on the thinking of Habermas and his theory of the interest of knowledge as well as de Holy Scripture where we find support for this spiritual counselling. This six-handed article has been written from the philosophical and theoretical perspective, but also practical and experiential (both medical and nursing) perspective of accompaniment in palliative care.
Keywords: spiritual counselling; palliative care; Habermas; spirituality; philosophy-science- faith dialogue; interest of knowledge; religion and secularism